2018
DOI: 10.1111/epi.14609
|View full text |Cite
|
Sign up to set email alerts
|

Homomeric Kv7.2 current suppression is a common feature in KCNQ2 epileptic encephalopathy

Abstract: Objective: To gain insight into the mechanisms underlying KCNQ2 encephalopathy by examining the electrophysiologic properties of mutant Kv7.2 channels in different multimeric configurations. Methods: We analyzed the genotype-phenotype relationship in 4 patients with KCNQ2 encephalopathy and performed electrophysiologic analysis of M-currents mediated by homomeric Kv7.2 or heteromeric Kv7.2/Kv7.3 channels.Results: Negligible or no current was recorded in cells expressing homomeric E130K, W270R, or G281R de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 32 publications
7
26
0
Order By: Relevance
“…All other single-substituted Kv7.2 channels herein investigated were functional, and showed a rightward shift in their activation gating (Figure 5; Table 1), confirming that each residue plays a prevalent role in the stabilization of the Kv7.2 activated state. Consistent with our results is the LoF effect observed in Kv7.1 [45,46] or Kv7.2 [38,42] when the charges at E1, R4, R5, and R6 are neutralized or reversed.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…All other single-substituted Kv7.2 channels herein investigated were functional, and showed a rightward shift in their activation gating (Figure 5; Table 1), confirming that each residue plays a prevalent role in the stabilization of the Kv7.2 activated state. Consistent with our results is the LoF effect observed in Kv7.1 [45,46] or Kv7.2 [38,42] when the charges at E1, R4, R5, and R6 are neutralized or reversed.…”
Section: Resultssupporting
confidence: 92%
“…The Kv7.2 E2Q mutation has been identified de novo on a single Kv7.2 allele; thus, homomeric channels composed of only mutant subunits represent a very small proportion of channels formed in vivo. Furthermore, while most I KM in adult superior cervical ganglion neurons are Kv7.2/Kv7.3 heterotetramers [34], expression of Kv7.2 precedes that of Kv7.3 in both rodent and human brains [35,36,37], and the severity of the Kv7.2 encephalopathy has been correlated to a mutation-induced dysfunction of homomeric Kv7.2 channels, possibly because of their critical role in fine-tuning neuronal connections during development [38]. Therefore, Kv7.2 E140Q subunits were co-expressed both with wild-type Kv7.2 subunits and wild-type Kv7.2 and Kv7.3 subunits.…”
Section: Resultsmentioning
confidence: 99%
“…6), which is shown to play critical roles in M-current expression and inhibition of hippocampal neuronal excitability 53 . Current suppression of homomeric channels is a common feature of EE variants of KCNQ2 54 . Given the overlapping distribution of K v 7.2 and K v 7.3 throughout the hippocampus and cortex 4 , the dominant negative functional effects of L268F and K552T variants on heteromeric channels (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction of the molecular model is compatible with the results of research on electrophysiological properties. Several studies have claimed that homomeric current change is common in KCNQ2 neonatal-onset EE 28,29,36,40 . In contrast, we found that heteromeric functional current changes are correlated with long-term neurodevelopmental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors contributing to long-term neurodevelopmental outcomes are multiple and complex, including genotype, genetic mosaicism, modified genes, duration of seizures, and environmental factors 6 8 , 37 . Homomeric current changes in KCNQ2 mutations were common in KCNQ2 mutations, suggesting loss of the ability to regulate neuronal firing 40 . However, in this study, the homomeric current changes were not necessarily associated with later neurodevelopmental outcomes.…”
Section: Discussionmentioning
confidence: 99%